2017
DOI: 10.1007/s11748-017-0788-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical case of isolated pulmonary valve endocarditis in a patient without predisposing factors

Abstract: We report a case of isolated pulmonary valve endocarditis in a 47-year-old woman without predisposing factors. She had episodes of low-grade fever and non-productive cough and was initially diagnosed with bacterial pneumonia. With antibiotic treatment, her condition improved transiently, but she had repeated respiratory events. Forty days after her first visit, she complained of severe dyspnea. Echocardiography revealed a large vegetation adhering to the pulmonary valve and she was diagnosed with isolated pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although most patients with PVE have been shown to respond well to appropriate antibiotic therapy, the role and timing of surgical therapy are not clear 3,4,11,12 . In general, persistent bacteremia or increased vegetation size (>2 cm) despite antibiotic therapy, recurrent embolism, severe pulmonary valve dysfunction secondary to valve destruction, and right heart failure are candidates for surgery 5,7,13–15 . According to previous data, 15%–30% of patients have required surgery, 14 but in the case series of 24 PVE by Isaza et al 5 between 2002 and 2018, surgery was required in the majority of patients (75%), particularly those with prosthetic PVE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most patients with PVE have been shown to respond well to appropriate antibiotic therapy, the role and timing of surgical therapy are not clear 3,4,11,12 . In general, persistent bacteremia or increased vegetation size (>2 cm) despite antibiotic therapy, recurrent embolism, severe pulmonary valve dysfunction secondary to valve destruction, and right heart failure are candidates for surgery 5,7,13–15 . According to previous data, 15%–30% of patients have required surgery, 14 but in the case series of 24 PVE by Isaza et al 5 between 2002 and 2018, surgery was required in the majority of patients (75%), particularly those with prosthetic PVE.…”
Section: Discussionmentioning
confidence: 99%
“…In general, persistent bacteremia or increased vegetation size (>2 cm) despite antibiotic therapy, recurrent embolism, severe pulmonary valve dysfunction secondary to valve destruction, and right heart failure are candidates for surgery 5,7,13–15 . According to previous data, 15%–30% of patients have required surgery, 14 but in the case series of 24 PVE by Isaza et al 5 between 2002 and 2018, surgery was required in the majority of patients (75%), particularly those with prosthetic PVE. They also showed that patients with congenital heart diseases had a better prognosis than others with PVE.…”
Section: Discussionmentioning
confidence: 99%